Crime and justice research: The current landscape and future possibilities. (September 2020) - Sparks, Richard
The contributions in this themed section developed from conversations that took place at an event hosted by the British Society of Criminology and Criminology & Criminal Justice in April 2019. The papers that follow respond to a 'think-piece' presented by Richard Sparks at that event, and engage with the subsequent debate about the future of funding for crime and justice research. Contributors reflect on the opportunities and challenges arising from recent shifts in funding allocations and priorities, from their different vantage points. Highlighting the importance of interdisciplinary and international work, they consider priorities for future investment in crime and justice research and draw attention to the impact of an increasingly restrictive and risk-averse climate on critical research. The papers explore the consequences for criminology as a discipline and warn of the potential reinforcement of existing inequalities in academia unless action is taken to support the development of future researchers.